2019
DOI: 10.21276/ap.2019.8.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Original article Thin-layer chromatography and in vitro free radical scavenging activity of few medicinal plants from the surroundings of Junagadh, Gujarat, India

Abstract: A collection of medicinal plants was done from the ambience of Junagadh district, Gujarat, India. These plants were subsequently screened to know their phytochemical potential. The in vitro antioxidant activity was also evaluated using DPPH and nitric oxide scavenging methods. Qualitative phytochemical screening and total phenolic content have been evaluated for each plant extract. TLC showed the presence of various phytochemicals like alkaloids, flavonoids, phenolics, glycosides, saponins, sterols and tannins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It is postulated that antioxidant activity is mainly due to the phenolic content present in the plant. As an important phytochemical bearing very reactive hydroxyl group, phenolics have attributed antioxidant action (Bidchol et al, 2011;Bhatt et al, 2019a). In this study, in vitro antiinflammatory activity has not been seen with fruits of L. echinata.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It is postulated that antioxidant activity is mainly due to the phenolic content present in the plant. As an important phytochemical bearing very reactive hydroxyl group, phenolics have attributed antioxidant action (Bidchol et al, 2011;Bhatt et al, 2019a). In this study, in vitro antiinflammatory activity has not been seen with fruits of L. echinata.…”
Section: Discussionmentioning
confidence: 63%
“…Saurashtra region of Gujarat is a large biodiversity region with several medicinal plants. Since a long time, these medicinal plants are used in the ethnoveterinary practices as well as in the ailments of human or animals (Bhatt et al, 2019a). The main advantages of medicinal plants are, they are economical, readily available and has no side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Coriandrum sativum L. and Spilanthes acmella L. was investigated by Bala et al, (2019), Kumari et al, (2019), Jeya et al, 2019 andThakur et al, (2019), using DPPH free radical scavenging assay. Bhatt et al, (2019) selected some plants from Junagadh, Gujarat for their antioxidant activity analysis and concluded that among all plants and different solvent extracts, aqueous extract of Peltophorum pterocarpum (DC.) K. Heyne and Syzygium cumini (L.) Skeels leaves presented highest DPPH radical scavenging ability while all the extracts of Bauhinia variegate L. Nag et al, (2019), using DNA protection assay for their antioxidant potential.…”
Section: Two Indian Medicinal Plants Viz Adhatodam Vasicamentioning
confidence: 99%